2012
DOI: 10.4049/jimmunol.1200702
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Generated against Conserved Antigens Expressed by Bacteria and Allergen-Bearing Fungi Suppress Airway Disease

Abstract: There has been a sharp rise in allergic asthma and asthma-related deaths in the developed world, in contrast to many childhood illnesses that have been reduced or eliminated. The hygiene hypothesis proposes that excessively sanitary conditions early in life result in autoimmune and allergic phenomena because of a failure of the immune system to receive proper microbial stimulation during development. We demonstrate that Abs generated against conserved bacterial polysaccharides are reactive with and dampen the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 78 publications
4
30
0
Order By: Relevance
“…Exposure to particular bacterial antigens during early life can alter the numbers of these developing clones and permanently select them in to the adult repertoire (9). We have previously demonstrated that altered antigen-specific B cell responses, following neonatal immunization with bacterial vaccines containing polysaccharide or phospholipid moieties shared by Aspergillus fumigatus fungi or house dust mite (HDM), suppress allergic disease development in adult animals (15, 16). …”
Section: Introductionmentioning
confidence: 99%
“…Exposure to particular bacterial antigens during early life can alter the numbers of these developing clones and permanently select them in to the adult repertoire (9). We have previously demonstrated that altered antigen-specific B cell responses, following neonatal immunization with bacterial vaccines containing polysaccharide or phospholipid moieties shared by Aspergillus fumigatus fungi or house dust mite (HDM), suppress allergic disease development in adult animals (15, 16). …”
Section: Introductionmentioning
confidence: 99%
“…at multiple stages of its life cycle (16). In this analysis, we observed that a previously described mouse mAb, SMB19, bound to A.f.…”
Section: Resultsmentioning
confidence: 99%
“…and fluorescence microscopy. [16] This mAb has been shown previously to bind to a sialylated oligosaccharide, s-LNT associated with the capsular polysaccharide of GBSIb (12). Other mAbs to members of this streptococcal group including GBSIa (SIaE7), GBSII (SIIF5C4), GBSIII, (SIIIV18), and desialylated GBSIb (SIbD2) (described in supplementary Table 1) do not bind either A.f.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations